A Bioresorbable Fiducial for Head and Neck Cancer. (September 2020) - Fischman, Victoria; Ivanovic, Vladimir; Jalisi, Scharukh
We aim to evaluate a novel bioresorbable fiducial for marking tumor bed margins in head and neck cancers (HNCs) to improve upon current use of nonresorbable materials. A feasibility test was done placing the marker (L-lactide and ε-caprolactone) in an orange for computed tomography (CT) and applesauce for T1-, T2-, and PD-weighted magnetic resonance imaging (MRI) image acquisition, using routine clinical parameters. The resulting CT and MRI images showed excellent delineation of the marker with all of its margins well seen without adjacent artifact. The marker appeared similar to air on CT and MRI, surrounded by fluid-like appearance of the medium. Surgical bed appearance when radiotherapy is planned should not produce any artifact near the marker, and there should be no inherent marker-related artifact. These pilot CT and MR images show clinical utility for intraoperative marking of positive margins in the skull base or neck to guide future treatment and monitoring.